Kloṅ chen sñiṅ gi thig le las : Thun moṅ gi sṅon ʼgro sems sbyoṅ rnam pa bdun daṅ Bla ma rgyaṅ ʼbod kyi rtsa ba rdo rjeʼi tshig ʼgrel ma bu lhan thabs man ṅag gi zab khrid sñiṅ poʼi bcud bsdus thar paʼi myur lam : instructions on the practice of the visionary Kloṅ chen sñiṅ thig teachings - Ṅag-gi-dbaṅ-po, Bde-chen-chos-ʼkhor Yoṅs-ʼdzin VIII (Tsering Paljor, 1975)
Instructions on precepts of Buddhist Dzogchen practice from the Kloṅ chen sñiṅ thig cycle of rediscovered teachings revealed by Jigs-med-gliṅ-pa Raṅ-byunṅ-rdo-rje, 1729 or 30-1798.